2016
DOI: 10.3390/genes7120116
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the Ubiquitin Conjugating Enzyme UBE2A in Alzheimer’s Disease (AD) is Linked to Deficits in a Natural Circular miRNA-7 Sponge (circRNA; ciRS-7)

Abstract: Our understanding of the highly specialized functions for small non-coding single-stranded RNA (ssRNA) in the transcriptome of the human central nervous system (CNS) continues to evolve. Circular RNAs (circRNAs), a recently discovered class of ssRNA enriched in the brain and retina, are extremely stable and intrinsically resilient to degradation by exonuclease. Conventional methods of ssRNA, microRNA (miRNA), or messenger RNA (mRNA) detection and quantitation requiring free ribonucleotide ends may have conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
232
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(242 citation statements)
references
References 34 publications
2
232
0
2
Order By: Relevance
“…Owing to its closed loop structure, circRNA is not degraded by RNA exonuclease, making it highly conserved and remarkably stable. Therefore, circRNA can be a potential diagnostic biomarker [20-22]. A previous study on hepatocellular carcinoma reported that ciRS-7 could be considered a biomarker for microvascular invasion in hepatic cell carcinoma and a sponge for microRNA-7 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its closed loop structure, circRNA is not degraded by RNA exonuclease, making it highly conserved and remarkably stable. Therefore, circRNA can be a potential diagnostic biomarker [20-22]. A previous study on hepatocellular carcinoma reported that ciRS-7 could be considered a biomarker for microvascular invasion in hepatic cell carcinoma and a sponge for microRNA-7 [23].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are also of paramount importance in many kinds of diseases and tumorigenesis. For instance, ciRS-7 depletion indirectly leads to a reduction of the ubiquitin conjugating enzyme UBE2A via excessive miRNA-7 in Alzheimer's disease [49]. The upregulation of hsa_circ_001569 and hsa_circ_0000069 augments cell proliferation, migration, and invasion, and hsa_circ_001988 downregulation is used as an indicator in colorectal cancer [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…However, one circRNA, ciRS‐7 , which acts as a sponge of miR‐7, was found to be lower in sporadic AD, as determined in the hippocampal CA1 region (Lukiw, ). In keeping with the idea that downregulation of ciRS‐7 may affect the availability of miR‐7 and hence the fate of miR‐7 target mRNAs, enhanced miR‐7 activity in AD brain due to low ciRS‐7 levels decreased the production of AD‐relevant miR‐7 targets, including the ubiquitin‐conjugating enzyme UBE2A and epidermal growth factor receptor (Zhao, Alexandrov, Jaber, & Lukiw, ). Furthermore, in SH‐SY5Y cells, ciRS‐7 was recently found to promote the degradation of APP and BACE1 in an NF‐κB‐dependent manner (Shi et al, ).…”
Section: Circular Rnas (Circrnas) In Admentioning
confidence: 74%